Commitment to environmental preservation in The Nglanggeran ancient volcano ecotourism area - Prasetyo, Andreas Yogi; Widanti, Eki Melina; Hidayah, Atika Nur (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study investigates the commitment to environmental preservation in the Nglanggeran Ancient Volcano Ecotourism Area, located in Gunungkidul, Yogyakarta, Indonesia. As a community-managed ecotourism destination experiencing rapid visitor growth, Nglanggeran presents a valuable case for examining the implementation of sustainable tourism principles in practice. The research aims to identify the extent to which environmental conservation strategies adopted by local management align with the core tenets of sustainable tourism. Using a qualitative descriptive method, data were collected through in-depth interviews with key stakeholders, direct field observations, and analysis of supporting documents. A purposive sampling approach was applied to select 12 participants actively involved in ecotourism and environmental management. Data were analyzed thematically to uncover patterns related to planning, biodiversity protection, waste management, and environmental education. Findings indicate that Nglanggeran’s management demonstrates a strong environmental ethic through practices such as ecological zoning, reforestation, collaborative conservation efforts, and the integration of education into tourism experiences. These initiatives reflect a practical application of sustainable tourism at the grassroots level. However, challenges remain in areas such as waste reuse and recycling, which require further community engagement and institutional support. This study contributes theoretically by contextualizing sustainable tourism in a localized, community-driven setting, and offers practical insights for policymakers and tourism stakeholders aiming to replicate such models in other destinations.